Comparison of medical versus surgical management of liver lobe torsion in rabbits - Sibbald, Rachel (Veterinary Evidence, 2024)
PICO Question Does medical management of liver lobe torsion in rabbits reduce mortality compared with surgical intervention? Clinical bottom line Category of research Treatment. Number and type of study designs reviewed Six studies were appraised in total. This consisted of three retrospective cohort studies and three case series. Strength of evidence Weak. Outcomes reported Medical management carries a similar 7-day survival rate compared to surgical treatment; however, long-term morbidity and mortality is increased compared with surgery. Delayed diagnosis and severe anaemia negatively affect outcomes of both groups. Conclusion Medical management does not reduce mortality compared with surgical treatment and within the literature there appears to be a preference for surgery when treating rabbits with liver lobe torsion. How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.